THERMODYNAMIC AND KINETICS STUDIES FOR THE SULFUR-FIXING ROASTING OF ANTIMONY SULFIDE USING ZnO AS SULFUR-FIXING AGENT (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Currently, the commercial antimony metallurgy is mainly based on pyrometallurgical process and oxidative volatilisation of Sb2S3 is an essential step. It has the problems of high energy consumption and low concentration of SO2 pollution. Aiming at these problems, we presents a new method of sulfur-fixing roasting of antimony sulfide. This method uses ZnO as a sulfur-fixing agent and roasting with Sb2S3 at 673K~1073K to produce Sb2O3 and ZnS. By studying the thermodynamics of the reactions, we can conclude that the ΔGθ of roasting reaction is below than -60kJ/mol and the predominance areas of Sb2O3 and ZnS are big and right shifting with the temperature increasing, which are all indicated that this method is theoretically feasible. The reacted products between Sb2S3 and ZnO indicated that the reaction began in the 773K and finished basically at 973K. We used the Ozawa-Flynn-Wall, Kissinger and Coats-Redfern method to calculate the kinetics of the roasting reaction. The conclusion is as follows: The average values of apparent activation energy (E) and natural logarithmic frequency factor (lnA) calculated by Ozawa-Flynn-Wall, Kissinger and Coats-Redfern were 189.72 kJ.mol-1 and 35.29 s-1, respectively. The mechanism of this reaction was phase boundary reaction model. The kinetic equation is shown as follow: